Nippur I: Temple of Enlil, Scribal Quarter, and Soundings. Excavations of the Joint Expedition to Nippur (1948-1952) of The University Museum of Philadelphia and The Oriental Institute of the University of Chicago - McCown, Donald E. (1967)
133s.; I. The Temple of Enlil. The Structural Remains, by R. C. Haines. Observations and Interpretation, by D. E. McCown; II. Private Houses in the Scribal Quarter. The Structural Remains, by R. C. Haines. The Dating, by D. E. McCown. The Objects (Pottery; Stone, Glass, and Metal Vessels; Glyptic; Baked-Clay Figurines, Plaques, and Models; Sculpture; Personal Ornaments; Other Small Objects), by D. E. McCown; The Burials, by D. E. McCown. Observations and Conclusions, by D. E. McCown. III. The Soundings. The Structural Remains, by R. C. Haines; The Objects, by D. E. McCown. The Topography of Eastern Nippur, by D. E. McCown.